CS-PEI/Beclin-siRNA Downregulate Multidrug Resistance Proteins and Increase Paclitaxel Therapeutic Efficacy against NSCLC - Wangta Liu; Yu-Lun Lo; Chin Hsu; Yi-Ting Wu; Zi-Xian Liao; Wen-Jeng Wu; Yi-Jou Chen; Chieh Kao; Chien-Chih Chiu; Li-Fang Wang (Elsevier, 2019)
Paclitaxel (PTX) is a widely used chemotherapy drug; however, frequent use causes multidrug resistance (MDR), which limits the utility of PTX against advanced non-small-cell lung cancer (NSCLC). PTX-resistant subline (NCI-H23-TXR) was established in vitro by exposing NCI-H23 cells to gradually increased concentrations of PTX in culture medium. Distinct Beclin expression of autophagy level was observed between resistant NCI-H23-TXR and parental NCI-H23 cells. Beclin-small interfering RNA (siRNA) was selected to restore sensitivity of PTX against NCI-H23-TXR. Chondroitin sulfate-polyethylenimine (CS-PEI) was constructed for delivery and protection of Beclin-siRNA. To delineate the underlying molecular mechanism of Beclin knockdown, we analyzed different MDR expression proteins of two cells using western blot, and the corresponding genes were confirmed by real-time PCR. Compared with NCI-H23, NCI-H23-TXR had higher expression levels in P-glycoprotein (P-gp) and multidrug resistance protein 7 (ABCC10). Knockdown of Beclin simultaneously inhibited P-gp and ABCC10, and renewed the sensitivity of PTX against NCI-H23-TXR. Research on zebrafish embryos revealed that tumor sizes decreased in NCI-H23 tumor xenografts but remained intact in NCI-H23-TXR tumor xenografts as zebrafish were treated with 1 μg/mL PTX. In contrast, the tumor sizes decreased in NCI-H23-TXR tumor xenografts with zebrafish pre-transfected with CS-PEI/Beclin-siRNA followed by the same treatment of PTX. The role of autophagy was associated with MDR development. This study paves the way for a new avenue of PTX in MDR-related lung cancer therapy using CS-PEI as a gene delivery carrier. Keywords: autophagy, Beclin-siRNA, multidrug resistance, MDR, non-viral gene delivery vector, paclitaxel, PTX